2016
DOI: 10.1115/1.4034541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impeller Squealer Tip on Centrifugal Compressor Performance

Abstract: This paper summarizes the main results sorted out from a design of experiment (DoE) based on a validated computational fluid dynamics (CFD). Several tip recessed geometries applied to an unshrouded impeller were considered in conjunction with two tip clearance levels. The computations show that recessed tip geometries have positive effects when considering high-flow coefficient values, while in part-load conditions the gain is reduced. Starting from the results obtained when studying tip cavities, a single rim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Increase in squealer cavity depth reduces performance [126], while the increase in squealer cavity width improves it [126]. The study conducted by Da Soghe et al [126] indicated that the best efficiency gain was achieved with the squealer depth of 15% of the blade thickness and with the squealer width of 80% of the blade thickness.…”
Section: Squealers and Winglets (Classification: Passive Geometric)mentioning
confidence: 97%
See 3 more Smart Citations
“…Increase in squealer cavity depth reduces performance [126], while the increase in squealer cavity width improves it [126]. The study conducted by Da Soghe et al [126] indicated that the best efficiency gain was achieved with the squealer depth of 15% of the blade thickness and with the squealer width of 80% of the blade thickness.…”
Section: Squealers and Winglets (Classification: Passive Geometric)mentioning
confidence: 97%
“…Increase in squealer cavity depth reduces performance [126], while the increase in squealer cavity width improves it [126]. The study conducted by Da Soghe et al [126] indicated that the best efficiency gain was achieved with the squealer depth of 15% of the blade thickness and with the squealer width of 80% of the blade thickness. The study of Li et al [129] indicated that the best efficiency gain is achieved with the squealer depth of three times the tip clearance (1.38 mm) when the squealer is as wide as possible.…”
Section: Squealers and Winglets (Classification: Passive Geometric)mentioning
confidence: 97%
See 2 more Smart Citations
“…They observed increase in energy coefficient and efficiency with squealer tips on pressure or suction surface. Recently Da Soghe et al [14] carried out numerical studies on the effects of various tip recessed geometries at two values of tip clearances on the performance of a transonic centrifugal compressor. Based on the results, further computations were carried out with a single rim tip squealer geometry, which had shown performance improvements for all the computed conditions.…”
Section: Introductionmentioning
confidence: 99%